Surveillance of Antimicrobial Susceptibility and Resistance Among Enterobacteriaceae Isolates from The Clinical Specimens in Secondary Referral Hospital: Pharmaceutical Science-Pharmacy Practice - Reddy, Raghu Prakash; Kumar, Dcs Naveen; Gonuguntla, Harshitha; Mandala, Sai Tharun Vijay; Goruntla, Narayana; Sahithi, Bogireddy (International Journal of Life Science and Pharma Research, 2022)
The aim of our study is to assess the pattern of antimicrobial susceptibility and resistance to the bacterial pathogens isolated from patient specimens. The main objectives are to evaluate the pattern of antimicrobial susceptibility and resistance to the bacterial pathogens isolated from patient specimens, to determine the proportion of antimicrobial sensitivity and resistance against specific antibiotics by bacterial pathogens isolated from various specimens collected and to assess the difference in Resistance of bacterial isolates to various antibiotics within different years. Emergence of antimicrobial resistance is a major public health problem worldwide. Antimicrobial resistance is one of the ten threats identified by the World Health Organization in 2019. Approximately 0.7 million people die every year from AMR. The WHO estimates 350,000,000 deaths could be caused by AMR by 2050. For three years the retrospective observational study was conducted among all the age groups of people. Antibiograms were used based on CLSI guidelines. A total of 2430 samples, 1226 males and 1204 females, are there. The samples were collected by different types like Urine Blood, Pus, Tissue culture, Stool culture, swab culture, CSF, and other fluids. Among all the isolated bacteria E. coli, Klebsiella, and Enterobacter were more isolated and were more resistant to the penicillins and cephalosporins category of drugs. The study shows that isolated gram-negative bacteria were resistant to ampicillin, amoxicillin, cephalothin, ciprofloxacin, cefuroxime, cefepime, ceftazidime, and ceftriaxone. So, these drugs can be replaced with organism-sensitive antibiotics like amikacin, chloramphenicol, colistin, and gentamicin to treat bacterial infections. When compared to year to year, the resistance will be increased.